Brand Image and Social Media Marketing on Purchase Decisions: The Mediating Role of Purchase Intention - Pratama, Nico; Lukitaningsih, Ambar; Fadhilah, Muinah (International Journal of Economics Development Research (IJEDR), 2024)
This study was conducted in the city of Yogyakarta with a sample of 126 Aerostreet Shoe users who had made a purchase at least 1 time. Data processing using SPSS, with the criteria of respondents having a minimum age of 17 years, the last education is high school, and have made a purchase of Aerostreet Shoes. The purpose of this study was to determine the effect of Brand Image, Social Media Marketing, and Purchase Intention, on Purchase Decision. The results showed that Brand Image, Social Media Marketing, Purchase Intention have a significant positive effect on Purchase Decision.